Proposal of a Microservice Plug-and-Produce Architecture for Industry 4.0 - Pontarolli, Ricardo P. [UNESP]; Viana, Eduardo A. [UNESP]; Giglio, Roger T. [UNESP]; Sisinni, Emiliano; Ferrari, Paolo; Godoy, Eduardo P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Industry 4.0 (I4.0) guided the evolution of control and automation architectures towards service orientation, Cloud Computing, Edge Computing, and Industrial Internet of Things seeking to provide greater modularity, vertical integration, and connectivity. The current research is focusing on developing and standardizing information models, management of industrial assets, the creation (composition) and management of industrial applications based on services. This paper proposes and presents a microservice Plug-and-Produce (PnPr) architecture for automation in I4.0 systematized in two processes. The Plug process covers the stages of modeling, aggregating, servitizing, installing and discovering, with a focus on the commissioning and discovery of assets. The Produce process covers the stages of communicating, selecting, analyzing, composing, and managing, with a focus on the composition of assets for creating applications. On the Plug part, it is described the modeling of the asset based on the Asset Administration Shell (AAS) standard, the logical programming, discovery as a microservice, the installation and management using container technology. In the Produce part, it is proposed to orchestrate applications through the composition of assets via OPC UA and microservices communication. Our proposal is discussed showing that the PnPr architecture is a viable solution for universalization of access to industrial assets, in addition to leverage the creation of I4.0 applications.
Keywords: Automation Architecture; Information Model; Orchestration; Process Control